2017
DOI: 10.5194/bg-14-2891-2017
|View full text |Cite
|
Sign up to set email alerts
|

The effect of drought on dissolved organic carbon (DOC) release from peatland soil and vegetation sources

Abstract: Abstract. Drought conditions are expected to increase in frequency and severity as the climate changes, representing a threat to carbon sequestered in peat soils. Downstream water treatment works are also at risk of regulatory compliance failures and higher treatment costs due to the increase in riverine dissolved organic carbon (DOC) often observed after droughts. More frequent droughts may also shift dominant vegetation in peatlands from Sphagnum moss to more drought-tolerant species. This paper examines the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 65 publications
4
34
1
Order By: Relevance
“…The gaseous C balance shows that both plant communities act as C sinks, with storage of 30 g C m −2 yr −1 in Sphagnum plots and 223 g C m −2 yr −1 in Sphagnum + Molinia plots. These results contrast with the assumption mentioned in the Introduction that vascular plants could lead to a decrease in C sequestration (Strakova et al, 2011). Nevertheless, the C-sink function of Molinia-dominated peat mesocosms can be questioned in view of the biomass production of Molinia caerulea.…”
Section: Annual C Fluxes and Ggcbcontrasting
confidence: 74%
See 3 more Smart Citations
“…The gaseous C balance shows that both plant communities act as C sinks, with storage of 30 g C m −2 yr −1 in Sphagnum plots and 223 g C m −2 yr −1 in Sphagnum + Molinia plots. These results contrast with the assumption mentioned in the Introduction that vascular plants could lead to a decrease in C sequestration (Strakova et al, 2011). Nevertheless, the C-sink function of Molinia-dominated peat mesocosms can be questioned in view of the biomass production of Molinia caerulea.…”
Section: Annual C Fluxes and Ggcbcontrasting
confidence: 74%
“…are expected to cause a plant community shift in peatlands, with an increase in vascular 4086 F. Leroy et al: CO 2 and CH 4 budgets and global warming potential modifications plants (especially graminoids) to the detriment of Sphagnum species (Berendse et al, 2001;Buttler et al, 2015;Dieleman et al, 2015). Vascular plant invasion could lead to a faster decomposition of peat OM due to a change in litter quality as a substrate for decomposers, thereby decreasing C sequestration (Strakova et al, 2011). Furthermore, OM already stored in deep peat may be subject to increased decomposition through the stimulating effect of rhizospheric C input (Girkin et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Samples may have been exposed to more extreme drying conditions than under field conditions as moisture levels were not regulated by living vegetation and/or underlying water table, and the lack of a peat substrate beneath the samples from the vegetation groups could also have increased the loss of water and so negated any rainfall treatment effect. Ritson et al (2017) found that any exposure to oxygen (during laboratory experiments) increased DOC from peat and changed the quality of the C.…”
Section: Limitations Of the Studymentioning
confidence: 97%